The Oxford Handbook of Psychiatric Ethics, Volume 1 - Werendly van Staden, Cornelius (Oxford University Press, 2014)
Psychiatrists have written much about the explosive expansion of scientific knowledge of the brain which developed over the late 20th century and the early 21st century. Comparatively little has been written within the field of psychiatry about the changes in society and world culture over this same period, and even less on the scope of psychiatric ethics that would account for these changes. Yet psychiatric ethics is an excellent framework in which to examine social changes in the field over the past 25 years, changes which are dramatic in nature and profound in impact. Some of these social changes include multiculturalism and its associated diversity of values; the transition to the digital era with its new demands on confidentiality, clinical boundaries, and privacy; the empowerment of psychiatric service users as full participants and co-producers of care; the development of new technologies of assessment and treatment, varying in their invasiveness and risk; the recognition of expanded social roles for psychiatrists, and the associated virtues of psychiatric citizenship; and the development of new practice models, settings, participants, and oversight, all of which represent profound challenges and opportunities for the ethical practice of psychiatry. The Oxford Handbook of Psychiatric Ethics is the most comprehensive treatment of the field in history. The volume is organized into ten sections which survey the scope of the text: (1) Introduction, (2) People Come First, (3) Specific Populations, (4) Philosophy and Psychiatric Ethics, (5) Religious Contexts of Psychiatric Ethics, (6) Social Contexts of Psychiatric Ethics, (7) Ethics in Psychiatric Citizenship and the Law, (8) Ethics of Psychiatric Research, (9) Ethics and Values in Psychiatric Assessment and Diagnosis, (10) Ethics and Values in Psychiatric Treatment. Written and edited by an international team of experts, this landmark book provides a powerful and important review of psychiatric ethics in the 21st Century.